Vats lobectomy for lung cancer. What has been the evolution over the time? - Re Cecconi, Emanuela; Mangiameli, Giuseppe; De Simone, Matilde; Cioffi, Ugo; Marulli, Giuseppe; Testori, Alberto (Frontiers in Oncology, 2024)
Video assisted thoracic surgery (VATS) lobectomy is the treatment of choice for early-stage lung cancer. It is safe and effective compared to open surgery, as demonstrated by a large body of scientific evidence over the last few decades. VATS lobectomy’s evolution was driven by the need to decrease post-operative pain by reducing the extent of surgical accesses, maintaining the same oncological efficacy of open lobectomy with less invasiveness. VATS lobectomy just turned 30 years old, evolving and changing significantly from its origins. The aim of this mini review is to retrace the history, starting from a multiport approach to a single port approach. At the end of this mini review, we will discuss the advanced and the future challenges of the technique that has revolutionized thoracic surgery.